Determination of Protein Amount in Nanosized Synthetic Liposomes by Surface Effect Raman Spectroscopy (SERS) - Şeyma Parlatan (Journal of Advanced Research in Natural and Applied Sciences)
Accurate characterization of synthetic liposomes is essential since they give information about the vesicu-lar structures in bodily fluids such as extracellular vesicles. The characterization tasks are generally the determination of the sizes of the liposomes and the profiling of the liposomes' content. Optical tweezers and Surface Enhanced Raman Spectroscopy (SERS) were used to profile the nanosized liposomes. The size distribution of the trapped liposomes (140 nm on average) was found by using Einstein's Brownian motion equation, consistent with the size distribution obtained from dynamic light scattering measure-ments. Besides, Gramicidin-encapsulated liposomes were measured using SERS, and statistically signifi-cant differentiation was found in Raman intensities between liposome populations with altering concentra-tions of proteins. This study uniquely measured size distributions of nano-sized liposomes with conven-tional optical tweezers (without plasmonics) and determined the chemical differences between empty and protein encapsulated liposomes with high accuracy using Raman spectroscopy